Plant tannin interactions during Phytophthora ramorum infection - Stong, Rachel A., author; Vivanco, Jorge M., advisor; Manter, Daniel K., advisor; Holm, David G., committee member; Leach, Jan E., committee member (Colorado State University. Libraries, 2013)
Phytophthora ramorum, the responsible agent of "Sudden Oak Death" and the infection of over 100 different plants has the potential to disrupt oak forests leading to devastating consequences. Resistance to P. ramorum varies by pathogen race or plant cultivar, plant species or genus, plant non-host and partial resistance. During infection, P. ramorum produces a 10 kDa elicitor protein, i.e., elicitin, that can induce plant defenses. P. ramorum uses elicitins to acquire sterols from plants since the pathogen does not synthesize sterols. Factors influencing host resistance are largely unknown, although phytochemicals, such as phenolics, are found to influence resistance to P. ramorum. Tannins, a group of polyphenolic compounds found in plant tissues are able to precipitate proteins, such as elicitins. The studies presented here investigate the possibility of an elicitin-sterol-tannin interaction in plant resistance to P. ramorum. This research includes a series of in vitro and in vivo studies of sterol and tannin interactions with P. ramorum. To explore the impact tannins may have on P. ramorum, media was treated with ground foliage, extracted tannins, or extracted sterols from three different tree types (Oregon white oak, California black oak and California bay laurel), or commercially-available sterols. Growth and sporulation of P. ramorum were higher on California bay laurel treatments as compared to the oaks. High concentrations of foliage from the oaks resulted in more rapid inhibition of P. ramorum growth and sporulation. Inhibition of P. ramorum growth and sporulation was also observed in response to plant sterols or tannins. This inhibition appears to be caused by two different mechanisms. Treatment with high concentrations of sterols reduced elicitin gene expression indicating a regulatory role. Tannins caused a decline in the amount of ELISA- detectable elicitin while there was no change seen in elicitin gene expression. All treatments showed a strong correlation between elicitin contents and P. ramorum growth and sporulation, suggesting a role for elicitin-sterol-tannin complexes in P. ramorum growth and sporulation in foliage. In a second study, several evergreen varieties of Rhododendron, Kalmia and Azalea were assessed for constitutive tannin content, sterol content and leaf susceptibility to P. ramorum. Significant differences were seen between the different species and between the two trials for tannin content. Variation of sterol content was only seen in Kalmia plants. Azalea plants showed no susceptibility to P. ramorum, while susceptibility varied between trial 1 and trial 2 for Rhododendron and Kalmia varieties. Variation of tannin and leaf susceptibility was also seen between cultivars. A positive correlation between all tannin data and lesion size suggests a relationship between tannin and P. ramorum. We propose that the formation of elicitin-sterol-tannin complexes inhibits plant defense responses allowing for greater pathogen colonization and lesion development.